Structural behavior of seawater sea-sand concrete shear wall reinforced with GFRP bars. (15th June 2019) - Zhang, Qingtian; Xiao, Jianzhuang; Liao, Qingxiang; Duan, Zhenhua
Highlights: Seawater sea-sand concrete (SSC) shear wall reinforced with GFRP bars is studied. Effect of SSC and GFRP reinforcement on seismic behavior of shear wall is explored. Theoretical analysis of flexural and shear capacity of SSC shear wall reinforced with GFRP bars is carried out. The feasibility of using FRP bars in SSC shear wall is evaluated. Abstract: This paper investigates the seismic performance of seawater sea-sand concrete (SSC) shear wall reinforced with glass fiber reinforced plastic (GFRP) bars. Three shear wall specimens were designed for the seismic performance evaluation, including natural aggregate concrete (NAC) reinforced with steel bars (SNW), NAC reinforced with GFRP bars (GNW) and SSC reinforced with GFRP bars (GSW). The results show that the application of SSC seems to have a negligible effect on the seismic performance of shear wall in the short term. The GNW and GSW have similar failure patterns and shapes of hysteresis curves. Also, with the same reinforcement ratio, the bearing capacity of GFRP reinforced specimens can be over 85% that of SNW while the deformability can reach the lateral drift up to 1/50. The ductility of GFRP reinforced specimen is lower than that of steel reinforced specimen but its residual deformation is relatively smaller. Furthermore, the applicability of existing design methods on the SSC shear wall is also evaluated.